MOTHERS’ PERCEPTION OF MIDWIFE SUPPORT IN THE PROVISION OF BREASTFEEDING IN BULELENG BALI - Kadek Ayu Suarmini; Luh Ayu Purnami; Putu Dian Prima Kusuma Dewi; Mochamad Heri; Putu Sukma Megaputri; Kadek Indah Novi Lestari (AIPKIND (Asosiasi Pendidikan Kebidanan Indonesia), 2020)
This study emphasizes the perception of nursing mothers towards the support of midwives they receive regarding breastfeeding. This mixed-method study was done using a random sampling to determine the sample. The data in this study was obtained by distributing a questionnaire to the mothers of the babies. The quantitative data were analyzed using univariate by STATA software 12 S.E while the qualitative study was done to five midwives using an indept interview. The results obtained were that almost all mothers had a good perception of midwife support because they really received support since the antenatal period through antenatal classes. Therefore, it is recommended for midwives to be able to provide breastfeeding support early on, i.e., by conducting clear counseling about breastfeeding in the antenatal class